1982
DOI: 10.1177/027112148200200310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parents' play routines on imaginative play in their developmentally delayed preschoolers

Abstract: T HE EFFECT OF parents' play routines in home intervention programs on developmentally delayed youngsters was examined in a parent-child play home intervention pro gram. The goals of the program were (1) to work with parents on a weekly basis, (2) to show them how to work on imaginative play with their youngsters in the home, and (3) to compare the performance of these parents and their children with that of members of the control group using selected assessment measures. Showing parents how to work systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…A total of 277 parents were included across these 24 studies (see Table 2). One-hundred and ninety-two mothers and 53 fathers were included across 23 studies; 1 study did not report the gender of parent participants (Yawkey, 1982). Twelve studies (50%) did not report parent ages.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 277 parents were included across these 24 studies (see Table 2). One-hundred and ninety-two mothers and 53 fathers were included across 23 studies; 1 study did not report the gender of parent participants (Yawkey, 1982). Twelve studies (50%) did not report parent ages.…”
Section: Resultsmentioning
confidence: 99%
“… Note. SCRD = Single Case Research Design; SES = socioeconomic status; M = males (fathers); F = females (mothers); NR = not reported; HS = high school; Coll = college; Grad = graduate school. a This study reported that parents ranged from early 20s to early 50s. b The total males and females does not include the parents from Yawkey (1982) because the numbers of males and females were not reported. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These researchers stress the importance of helping infants and mothers develop satisfying, reciprocal play interactions, with the implication that the long-term effects so gained may be most helpful to the child over time. Linder (1982) and Yawkey (1982) suggest various ways of assisting parents to use interactive play rather than a more structured teaching approach to build both sensorimotor and symbolic cognitive skills, with affective benefits for both child and parent.…”
Section: Dyadic Interventionsmentioning
confidence: 99%